Fuel-flexible biomass off-gassing: The impact of antioxidant spent coffee grains on emissions of CO2, CO, CH4, and VOCs, physical deposits, and combustion in wood pellets - Moreira, Bruno Rafael de Almeida [UNESP]; Cruz, Victor Hugo [UNESP]; Barbosa Junior, Marcelo Rodrigues [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Silva, Rouverson Pereira da [UNESP] (Elsevier, 2024)
The surging global demand for sustainable energy has propelled the solid biofuel industry, particularly wood pellets. However, the industry grapples with persistent challenges involving off-gassing during storage and transportation. This study introduces an alternative: harnessing a biogenic extract from spent coffee grains (SCG) to manage emissions of carbon monoxide (CO), carbon dioxide (CO2), methane (CH4), and volatile organic compounds (VOCs). Our approach involves applying SCG extract to pinewood sawdust pellets in controlled volumes (0.1 L) and concentrations (0.05 %, 0.1 %, 0.2 %, and 0.4 employing an airbrush compressor for even distribution. To assess emissions, triplicate 0.1 kg samples were placed in gastight chambers at regulated temperatures (25, 35, and 50 °C) and humidity levels (30 %, 60 %, and 90 %). They were measured at five-day intervals over six months. Pellets with the antioxidant additive at 0.05 % exhibited approximately 18,269 ppm of gases (CO2, CO, CH4, and VOCs), compared to 21,039 ppm in untreated pellets, indicating a consistent 13.2 % reduction in total off-gassing. Specifically, CO concentrations in treated and untreated pellets were 3795 ppm and 5012 ppm, respectively, translating into a 24.3 % reduction. Significant reductions were also observed in CO2 (12.95 %), CH4 (19.35 %), and VOCs (5.45 %). Environmental factors, particularly humidity levels above 60% and elevated temperatures within the range of 35–50 °C, were identified as influencing factors in these emissions. This insight was elucidated through a conditional inference tree (CIT) analysis. Stakeholders can leverage these findings to optimize pellet storage and transportation practices, aligning with the global commitment to advancing sustainable energy solutions.
Keywords: Carbon dioxide; Carbon monoxide; Extractives; Methane; Volatile organic compounds